2011
DOI: 10.1016/j.pain.2011.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of presurgical expectancies in predicting pain and function one year following total knee arthroplasty

Abstract: The present study examined the prospective value of response expectancies (ie, pain, sleep) and behavioral outcome expectancies (ie, return to function) in the prediction of pain severity and functional limitations 12 months after total knee arthroplasty (TKA). The study sample consisted of 120 individuals (73 women, 47 men) with osteoarthritis of the knee who were scheduled for TKA. Measures of expectancies, pain severity, pain catastrophizing, pain-related fears of movement, and depression were completed pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
159
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 53 publications
6
159
4
2
Order By: Relevance
“…35 Furthermore, increased pain catastrophizing predicted increased pain and poor function one year following total knee arthroplasty. 36 Our data are the first to suggest that gabapentin may play a role in the reduction of pain catastrophizing and help reduce the negative effect caused by such thinking. Future studies might investigate pharmacological interventions aimed at decreasing pain catastrophizing to determine whether patients realize improvements in post-surgical pain and conceivably postoperative patient function.…”
Section: Discussionmentioning
confidence: 62%
“…35 Furthermore, increased pain catastrophizing predicted increased pain and poor function one year following total knee arthroplasty. 36 Our data are the first to suggest that gabapentin may play a role in the reduction of pain catastrophizing and help reduce the negative effect caused by such thinking. Future studies might investigate pharmacological interventions aimed at decreasing pain catastrophizing to determine whether patients realize improvements in post-surgical pain and conceivably postoperative patient function.…”
Section: Discussionmentioning
confidence: 62%
“…Lingard and Riddle [34] estimated the effect to be 3 to 5 points lower on the 20-point pain component of the WOMAC, indicating worse pain in the group of patients with lower mental health scores. Two studies [39,47] that examined the correlation between patient pain after TKA and the Pain Catastrophizing Scale found a statistically significant relationship. Riddle et al [39] found that a Pain Catastrophizing Scale score of 16 or greater predicted less than 50% improvement in WOMAC pain score (odds ratio [OR], 2.67; 95% CI, 1.2 À 6.1; p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining six studies did not examine these states specifically but showed that lower preoperative mental health scores had similar postoperative associations [8,9,13,27,46,47,50]. Pain scores in the patient population with anxiety, depression, or lower mental health scores were elevated at baseline and at all assessment points [13,27,28,34,37,47,50] for up to 2 years in one study [34 ]. Lingard and Riddle [34] estimated the effect to be 3 to 5 points lower on the 20-point pain component of the WOMAC, indicating worse pain in the group of patients with lower mental health scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations